Podcasts as a Digital Tool in Biology Teaching - Pedro Samuel Hernández Jiménez; Adelainy Nuñez Pérez; Anthony Acosta García; Caridad Josefa Rivero Casanova; Rafael Antonio Hernández Cruz Pérez (Scientia Publica Media, 2026)
The digital age of the 21st century offers new generations creative and motivating spaces within the teaching and learning process. These tools, such as interactive platforms and multimedia resources, encourage active exploration of knowledge, especially in subjects like biology. Podcasts are an innovative tool in science education. Therefore, this research aims to design a system of activities that uses podcasts as a teaching resource to improve learning in biology, specifically in Unit 2: The World of Living Things: Unique or Diverse?, in the seventh grade at the “José Martí” Secondary School in the municipality of Pinar del Río. The study was conducted using a mixed-methods approach, adopting the dialectical-materialist method; theoretical and empirical methods were employed; specifically, historical-logical methods were used to conduct a systematic review of the literature published between 2020 and 2026, following the PRISMA guidelines, which allowed for the identification of the impact of podcast use in biology education, as well as empirical methods that included observation, surveys, and interviews. The results highlighted certain limitations in the teaching and learning of biology in seventh grade, primarily the lack of digital resources and teaching materials, as well as the limited use of active learning methods by teachers, while student participation and motivation were only partially evident. However, 79% of students reported having access to devices for listening to and watching audio and video content, and 85% expressed a preference for using podcasts in class, considering them useful for improving learning of difficult content while making classes more dynamic and interactive. These findings highlight the need to implement innovative teaching strategies that integrate podcasts into biology instruction to enhance student motivation and participation, as well as the importance of providing methodological training to teachers to ensure the effective incorporation of digital resources into the educational process.